DIRECTIONS FOR ENSURING FINANCIAL PERFORMANCE IN THE PRIVATIZATION OF STATE-OWNED ENTERPRISES (International Conference on Modern Science and Scientific Studies, 2025)
This article examines the essential directions for ensuring the financial performance of state-owned enterprises (SOEs) during the privatization process. The study emphasizes the importance of strategic planning, financial restructuring, corporate governance reforms, and transparent valuation mechanisms in improving the financial health of enterprises transitioning from public to private ownership. The article also discusses global experiences and proposes practical recommendations for developing countries like Uzbekistan to enhance privatization outcomes.